Dünden Bugüne Fotoğraf - (:unkn) unknown (My University, 2005)
0

The historical past of the art of photography is handled in this study. Following the first studies on photography, the first photography exhibitions are dealt with. Besides, differences between photography and picture are included in the present study. The state of the art of photography which indicate the realities to day besides a rich narrator constitutes another part of this study.
Photography from Past Till Today
Keywords: Sanat